POLYACETYLENE COMPOUNDS IN SPECIES OF GENUS BIDENS - D. A. Konovalov; A. M. Nasukhova (Фармация и фармакология (Пятигорск))
In genus Bidens, as well as in family Asteraceae as a whole, different researchers had described polyacetylenes, sesquiterpene lactones and flavonoids. Interest to these classes of substances also has been caused by their antiparasitic, antifungal, antioxidant, cytotoxic and other properties.Within family Asteraceae polyacetylenes are widespread in tribe Heliantheae and genus Bidens. They are capable to be accumulated in all parts of plants of this genus though they have been most often found out in roots.In species of genus Bidens the most widespread are С17–, С14–, С13–polyacetylenes, and also aromatic derivatives and thiophenes.Other group of the polyacetylenes found out in species of the genus – polyacetylene glucosides. According to the majority of researchers of this group of polyacetylenes, the glycosidation is a way facilitating of transportation of typically lipophilic compounds. The majority of these polyacetylenes is revealed in species of genus Bidens.